EDPUZZLE COMO HERRAMIENTA DE APOYO EN EL APRENDIZAJE SIGNIFICATIVO DE LOS ESTUDIANTES DE LA CARRERA DE PEDAGOGÍA DE LAS CIENCIAS EXPERIMENTALES E INFORMÁTICA DE LA SECCIÓN MATUTINA, DE LA UNIVERSIDAD TÉCNICA DE BABAHOYO, PERÍODO ACADÉMICO ABRIL - AGOSTO 2024. - CAMPOS ARECHUA SOLANGE JANICSE (2024)
The objective of this research work was based on designing the strategy for using the Edpuzzle tool as support to strengthen the meaningful learning of the Pedagogy of Experimental Sciences and Computer Science students at the Technical University of Babahoyo, which began thanks to the teaching materials that the students use during classes, this digital tool will solve this problem and will help the student to have material linked to a real context and directed by information and communication technologies. The population valued for the development of this strategy was 239 students who belong to the Pedagogy of Experimental Sciences and Computer Science career. The type of research was quantitative, descriptive, applicative, adaptive and propositional. For this project, the survey technique was used in which a questionnaire of 12 closed questions was carried out using the Likert scale with five categories. It is concluded that this strategy favors the understanding of the activities, provides access to free content that allows strengthening knowledge; It also includes the integration of web technology, videos, questionnaire, artificial intelligence and tasks that can be performed within the platform that provide additional value to this material that will serve as a guide for students when they receive classes.